Influence of diabetes on plasma pharmacokinetics and brain bioavailability of grape polyphenols and their phase II metabolites in the Zucker diabetic fatty rat. Issue 10 (14th August 2017) - Chen, Tzu‐Ying; Ferruzzi, Mario G.; Wu, Qing‐Li; Simon, James E.; Talcott, Stephen T.; Wang, Jun; Ho, Lap; Todd, George; Cooper, Bruce; Pasinetti, Giulio M.; Janle, Elsa M.
Abstract : Scope: The effect of diabetes on the pharmacokinetics, bioavailability and brain distribution of grape polyphenols and select metabolites was studied in the Zucker diabetic fatty (ZDF) rat model. Methods and results: (ZDF) rats and their lean controls (LN) were dosed with a Standardized Grape Polyphenol (SGP) Mixture consisting of grape seed extract, Concord grape juice and resveratrol (RES) by oral gavage for 10 days. An 8‐h pharmacokinetic study was performed. After 24 h, a second dose of SGP was administered and 1 h later animals were sacrificed and brain tissue was harvested. Plasma, urine, and brain tissue were analyzed for grape polyphenols. ZDF rats exhibited significantly diminished Cmax for all catechin, epicatechin, quercetin and resveratrol conjugated metabolites. Bioavailability was significantly lower in ZDF rats for methylated flavan‐3‐ol, RES, and quercetin metabolites. Significantly lower levels of metabolites of RES, quercetin, and flavan‐3‐ols were found in brains of ZDF rats. There was no significant difference between ZDF and LN in anthocyanins in plasma and no anthocyanins were detectable in brain extracts. ZDF rats showed significantly higher urinary excretion for all polyphenols. Conclusion: Diabetes may alter the overall bioavailability of some polyphenols in plasma and brain in part due to higher urinary clearance. Abstract : Grape polyphenols may be beneficial in the prevention of Alzheimer's disease. Diabetics have an increased risk of Alzheimer's disease. Diabetic and normal Zucker rats are fed a mixture of grape polyphenols. The amount of polyphenols reaching the brains of diabetic rats is less than that of normal rats suggesting that it might be necessary to adjust to dose for diabetics to achieve efficacy.